The Secret River - Kate Grenville (Edinburgh Canongate Books Ltd, 2007)
In 1806 William Thornhill, an illiterate English bargeman and a man of quick temper but deep compassion, steals a load of wood and, as a part of his lenient sentence, is deported, along with his beloved wife, Sal, to the New South Wales colony in what would become Australia. "The Secret River" is the tale of William and Sal's deep love for their small, exotic corner of the new world, and William's gradual realization that if he wants to make a home for his family, he must forcibly take the land from the people who came before him. Acclaimed around the world, "The Secret River" is a magnificent, transporting work of historical fiction.
Keywords: Historicial Fiction - Australia History -- Historicial Fiction - Australia History